Characterization of toroidal intrinsic rotation with MHD activity in theTCABR tokamak - G. Ronchi (2015)
Plasma rotation has an important play in stabilization of MHD modes and reducing turbulenttransport of particles and energy. Because in fusion reactors it is expected the torque provided byexternal sources will be small, the intrinsic (or spontaneous) rotation is of great interest[1, 2, 3].Furthermore, the origin and physics of plasma rotation is also an important issue by itself.The behavior of the intrinsic toroidal rotation during the growth and saturation of m/n =2/1 magnetic islands, triggered by programmed density ramp up, has been investigated in Lmodeohmic discharges in the TCABR tokamak. In those discharges R = 0.61 m, a = 0.18 m,Ip 80 kA, Bt = 1.07 T, q(a) 3.5 and the toroidal spontaneous rotation of the plasma coreis in the counter-current direction. The results show that the plasma is accelerated as the islandstarts to grow, while the island frequency slows down. And, as the island saturates, the toroidalrotation decreases quite rapidly (faster than the island), and the discharge is followed by a majordisruption. In some discharges, where the density decreases after the island saturation (and thus,avoiding the plasma disruption), the MHD instability becomes smaller until it vanishes, and thetoroidal rotation slows down to its original value before the gas injection.